Peran Umur Tanam dan Asal Benih pada Pertumbuhan dan Hasil Garut (Marantha Arundinacea) - Jenni Tri Utami; Supriyono Supriyono; Sri Nyoto (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2018)
Arrowroot (Marantha arundinacea) is potential plant to be developed in Indonesia. Arrowroot usually grows wild without special treatment so that makes the productivity is low. The purpose of research was to find the suitable planting age and seeds origin of arrowroot. The research was conducted from October 2016 to November 2017 at Experimental Field of Agriculture Faculty of Universitas Sebelas Maret. The research used RCBD (Randomized Completed Block Design) with two factors.The treatment of planting age consist of 3 levels (1 month, 2 months, 3 months) and seeds origin consist of 2 levels (tuber seeds and seed of nursery), each is repeated 4 times with 3 plants each replication. The results showed that the planting age treatment at 1 month of planting age has the better result compared with other treatments in almost every variables observed i.e plant height, number of tillers, tuber lenght, diameter tuber, and tuber weight per plant. The number of leaves,fresh weight plant, dry weight plant, and number of tubers are not significantly different at 1 month of planting age, although the plant is higher. The highest lenght of tuber is 20,5 cm from 2 months of planting age. Tuber weight of planting age treatment reached 31,8–124,9 gram per plant. Seed of nursery showed better results than tuber seeds although not significanly different. Between planting age and origin of seeds was no interaction.